Nitrogen washing from C3 and C4 cover grasses residues by rain - Rosolem, Ciro Antonio [UNESP]; Werle, Rodrigo [UNESP]; Garcia, Rodrigo Arroyo [UNESP] (FapUNIFESP (SciELO), 2010)
Crop species with the C4 photosynthetic pathway are more efficient in assimilating N than C3 plants, which results in different N amounts prone to be washed from its straw by rain water. Such differences may affect N recycling in agricultural systems where these species are grown as cover crops. In this experiment, phytomass production and N leaching from the straw of grasses with different photosynthetic pathways were studied in response to N application. Pearl millet (Pennisetum glaucum) and congo grass (Brachiaria ruziziensis) with the C4 photosynthetic pathway, and black oat (Avena Strigosa) and triticale (X Triticosecale), with the C3 photosynthetic pathway, were grown for 47 days. After determining dry matter yields and N and C contents, a 30 mm rainfall was simulated over 8 t ha-1 of dry matter of each plant residue and the leached amounts of ammonium and nitrate were determined. C4 grasses responded to higher fertilizer rates, whereas N contents in plant tissue were lower. The amount of N leached from C4 grass residues was lower, probably because the C/N ratio is higher and N is more tightly bound to organic compounds. When planning a crop rotation system it is important to take into account the difference in N release of different plant residues which may affect N nutrition of the subsequent crop.
Lavagem do nitrogênio de resíduos de plantas C3 e C4 pela chuva
Keywords: Cover crops; Nitrogen fertilization; Nutrient cycling